(untitled) (SAARC Journal of Agriculture, 2020)
Necrotic enteritis (NE) is a major economic problem in broiler industry globally and is caused by Clostridium perfringens. The aim of the study was to know the effects of turmeric on C. perfringens in broiler chickens. A total of 3000-day-old Cobb 500 broiler chicks were divided into 6 groups and reared in environment control sheds with similar management. Each group contains 500 chicks and again divided into two subgroups as control and treatment with 250 chicks. In treatment groups added 2gm/kg turmeric powder with basal feeds and reared up to 30 days and follow standard vaccine schedule. Intestinal samples were collected every week from each group to detect C. perfringens load. Bodyweight gain, feed conversion ratio (FCR) and mortality rates were also calculated. The findings were loads of C. perfringens in treatment groups decreased significantly compared to control groups. At 4th week average count of C. perfringens was 4.44±0.12 log CFU/g and 2.68±0.17 log CFU/g in control and treatment groups, respectively. Average chick’s mortality decreased significantly in treatment groups. The flock mortality was decreased significantly in treatment groups (1.40%) compared to control groups (2.17%). The FCR become significantly decreased in treatment groups (1.490) compared to control groups (1.571). Therefore, use of turmeric powder in broiler ration can reduce NE by decreasing C. perfringens loads and it could be a good source of non-antibiotic growth promoter in poultry towards reduce antibiotic resistance and consumer will get a pathogen free rich protein source. SAARC J. Agri., 18(1): 209-218 (2020)